PDGFR‐α, PDGFR‐β, VEGFR‐2 and CD117 expression in canine mammary tumours and evaluation of the in vitro effects of toceranib phosphate in neoplastic mammary cell lines. (18th August 2018) - Gattino, Francesca; Maniscalco, Lorella; Iussich, Selina; Biasato, Ilaria; Martano, Marina; Morello, Emanuela; Gola, Cecilia; Millán Ruiz, Yolanda; Saeki, Nobuo; Buracco, Paolo; Martín de las Mulas, Juana; De Maria, Raffaella
Abstract : Canine mammary tumours (CMTs) are one of the most common malignancies in bitches. Platelet‐derived growth factor receptor (PDGFR) α and β, vascular endothelial growth factor receptor‐2 (VEGFR‐2) and CD117 are tyrosine kinase receptors involved in several tumours and represent suitable targets for specific therapy with toceranib phosphate. The purpose of this study was to evaluate the expression of these receptors in the pathogenesis and progression of CMTs. PDGFRα, PDGFRβ, VEGFR‐2 and CD117 were expressed in 46/83 (55.4 per cent), 33/83 (39.8 per cent), 46/83 (55.4 per cent) and 32/83 (38.5 per cent) of CMTs, respectively. Immunohistochemical results showed a statistically significant loss of PDGFRα and PDGFRβ expression in simple carcinomas compared with complex/mixed carcinomas. Protein expression by western blot revealed specific bands corresponding to PDGFRα and VEGFR‐2 in 3/7 and in 1/7 cell lines. Moreover, in vitro treatment showed that toceranib phosphate weakly reduced cell proliferation in one canine mammary cell line. Before considering TKR inhibitors for possible therapeutic approaches, actually further studies are necessary to evaluate the effect of these drugs on CMTs in vivo.